Meeting the challenges of retention and enrollment of study participants in clinical trials during the COVID-19 pandemic from the study leadership perspective: Experience from the Zoster Eye Disease Study (ZEDS) - MeeLee Tom (Elsevier, 2021)
Purpose: To describe steps taken that enabled a high rate of retention and early resumption of enrollment in the Zoster Eye Disease Study (ZEDS), a randomized controlled trial funded by the National Eye Institute, during the first 13 months (3/1/2020–3/31/2021) of the COVID–19 pandemic. Methods: A number of responses were implemented in ZEDS when the focus shifted to retention of study participants at the beginning of the pandemic including frequent communication with the participating clinical centers (PCCs) about remote visits, local lab work, shipping study medication, and completion of revised case report forms. Additional payments were provided to the PCCs. Remote activation of PCCs continued. Screening and enrollment visits gradually resumed when allowed. Results: Communication with PCCs increased, and average attendance at monthly coordinator teleconferences went up from 17 to 47. Remote visits peaked in April 2020, accounting for 75% (33/44) of study visits, then declined to less than 10% of study visits beginning August 2020. Overall, 97% (590/609) of study visits were completed. Only 5.5% (9/165) of study participants withdrew consent, and 2.4% (4/165) were lost to follow-up. Enrollment returned to pre-pandemic levels by September 2020. Discussion: Strong communication and unwavering commitment, combined with the technological capability for remote work, visits, and shipment of study medication, were key to the successful retention of study participants and resumption of enrollment. Conclusions: Rapid responses to challenges to trials caused by the COVID-19 pandemic can enable them to continue successfully and provide insights into the planning of future trials.